Using scenario analyses to address the future of food. (8th July 2019) - Benton, Tim G
Abstract: The food system was developed around a set of policy drivers to make food cheaper and more available, these included promoting agricultural productivity and global trade to increase the availability of food. However, as has been recognised by a plethora of recent papers and reports, these factors have also led to a food system that is unsustainable through its impacts on human health (particularly the growing obesity epidemic) and the environment (e.g. as a major driver of climate change). The world is changing at an unprecedented rate, and the food system is becoming increasingly 'just in time', spatially extended, and dependent on more facilitating sectors (water, land, transport, finance, cyber, etc.). This produces a degree of systemic fragility that drivers (like demand) can interact with events (e.g. a climate impact) to create the opportunity for large‐scale shifts in the way the world works. Given the unsustainability of the food system, and the uncertainty of how it may evolve, scenario analysis can be a useful tool for imagining plausible futures as an aid to unlocking 'business as unusual' thinking. Summarising a number of recent processes, I describe scenarios of countries' food systems shaped by changing patterns of trade and changing dietary patterns.